The Characterization of Enterococcus Genus: Resistance Mechanisms and Inflammatory Bowel Disease - Růžičková, Michaela; Vítězová, Monika; Kushkevych, Ivan (Open medicine (Warsaw, Poland), 2020)
The constantly growing bacterial resistance against antibiotics is recently causing serious problems in the field of human and veterinary medicine as well as in agriculture. The mechanisms of resistance formation and its preventions are not well explored in most bacterial genera. The aim of this review is to analyse recent literature data on the principles of antibiotic resistance formation in bacteria of the Enterococcus genus. Furthermore, the habitat of the Enterococcus genus, its pathogenicity and pathogenicity factors, its epidemiology, genetic and molecular aspects of antibiotic resistance, and the relationship between these bacteria and bowel diseases are discussed. So-called VREfm - vancomycin resistant Enterococcus faecium and its currently rapidly growing resistance as well as the significance of these bacteria in nosocomial diseases is described.
Keywords: Enterococcaceae; resistance; nosocomial diseases; vancomycin; Enterococcus faecium; antibiotics